2022
DOI: 10.3389/fped.2022.1037261
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration in glycemic control on schooldays among children and adolescents with type 1 diabetes: A continuous glucose monitoring-based study

Abstract: BackgroundTo investigate the effect of school life by comparing the glycemic control between holidays and schooldays in children and adolescents with type 1 diabetes (T1D).MethodsThis observational study enrolled school-aged students with T1D (aged 6–19) from September 2019 to July 2021. Continuous glucose monitoring (CGM) records were processed and divided into holidays and schooldays. Other information was collected via questionnaires. We compared the results using paired T-test, Wilcoxon paired test and log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…This might be due to the development of problem-solving and planning skills, increased motivation for self-care, and better communication with healthcare providers [ 17 ]. A study by Ding et al showed that better glycemic control was associated with better academic performance among children and adolescents with T1DM, and it suggested that better glycemic control may lead to improved cognitive function and increased school attendance, leading to better academic performance [ 18 ]. Our study found that children and adolescents with parents who had higher education levels scored significantly better in total QoL and treatment barriers, treatment adherence domains, and glycemic control than those who had parents with lower education levels.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the development of problem-solving and planning skills, increased motivation for self-care, and better communication with healthcare providers [ 17 ]. A study by Ding et al showed that better glycemic control was associated with better academic performance among children and adolescents with T1DM, and it suggested that better glycemic control may lead to improved cognitive function and increased school attendance, leading to better academic performance [ 18 ]. Our study found that children and adolescents with parents who had higher education levels scored significantly better in total QoL and treatment barriers, treatment adherence domains, and glycemic control than those who had parents with lower education levels.…”
Section: Discussionmentioning
confidence: 99%